IMPROVING THE USE OF SIMPLE PAST TENSE IN WRITING RECOUNT TEXT BY USING INDUCTIVE METHOD - Suriana, Suriana; Apriliaswati, Rahayu; Sutapa, Gatot (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The researcher conducted a research about teaching simple past tense in writing recount text by using inductive method. The purpose of this research was to investigate how inductive method improved the use of simple past tense in writing recount text. Based on the students’ problems in the class, the researcher used a classroom action research as the method of research. The subject of this research was the eighth grade students in class A of MTsN 2 Pontianak in academic year 2016/2017. The result of this research showed that there was an improvement of students’ correct use of simple past tense in writing recount text. It was known from the observation and students’ writing assessment. In conclusion, the use of simple past tense in writing recount text improved by using inductive method. This inductive method is recommended for the English teacher when she/he teaches simple past tense in writing recount text.. Keywords: Simple Past Tense, Writing, Recount Text, Inductive Method